ANALISIS POTENSI PENDAPATAN DARI MEKANISME REDD SEKTOR KEHUTANAN DI INDONESIA - Siswanto, Adrianus Dwi (Jurnal Kajian Ekonomi dan Keuangan, 2010)
Indonesia faces serious problems in the forestry sector. The forest area covers about 70 percent of the total area spread over 33 provinces, have been damaged more than 37 percent on many levels. Department of Forestry reported deforestation reached 1 million hectares per year since 2000. If the condition is not change then the year 2050 the entire forest will be gone.This study focus to calculate the value of potential income that can be accepted if the REDD mechanism is applied in Indonesia. The methodology used in this study are mathematics and descriptive statistics using secondary data. Source of data are obtained the Central Bureau of Statistics and Ministry of Forestry and other sources. The results showed that according the baseline, the growth trends in deforestation by using 2000 - 2005, Indonesian forest destruction reached 35.277 million hectares on 2017 with 15 percent growth assumption damage.By implementing 3 simulations assuming that the decreased the rate of deforestation by 15 percent, 50 percent and 75 percent, the study provides results that the potential revenue are vary from of U.S. $ 20.155 million to U.S. $ 532.530 million. Estimated potential revenue is determined by the ability to decrease the growth rate of deforestation. The higher the ability to decrease the rate of deforestation, the higher the potential for carbon stock is maintained. On the other side encouraging the increasing deforestation of forest produce higher emissions more carbon stock disappear.